Scientific misconduct encountered by APAME journals: an online survey - Looi, L.M.; Wong, L.X.; Koh, C.C. (2015)
In June 2015, invitations were sent by email to 151 APAME journals to participate in an online survey with an objective of gaining insight into the common publication misconduct encountered by APAME editors. The survey, conducted through SurveyMonkey over a 20-day-period, comprised 10 questions with expansions to allow anecdotes limited to 400 characters, estimated to take less than 10 minutes to complete. Only one invitation was issued per journal, targeting (in order of priority) editors, editorial board members and editorial staff, and limited by email availability. 54 (36%) journals responded. 98% of respondents held Editor or Editorial Board positions. All respondent journals have editorial policies on publication ethics and 96% provide instructions related to ethics. 45% use anti-plagiarism software to screen manuscripts, the most popular being iThenticate, CrossCheck and Turnitin. Up to 50% of journals had encountered studies without IRB approval. Author misconduct encountered were (in rank order): plagiarism (75%), duplicate publication (58%), unjustified authorship (39%), authorship disputes (33%), data falsification (29%), data/image manipulation (27%), conflict of interest (25%), copyright violation (17%) and breach of confidentiality (10%). Reviewer misconduct encountered were: conflict of interest (19%), plagiarism (17%), obstructive behavior (17%), abusive language (13%) and breach of confidentiality (13%). Notwithstanding the limitations of the survey and the response rate, a few insights have been gained: (1) the need for strengthening the ethical culture of researchers/authors and reviewers, (2) anti-plagiarism software can improve plagiarism detection by about 15%, and (3) the need for technical support to detect plagiarism, duplicate publication and image manipulation.